Odanacatib for the treatment of postmenopausal osteoporosis. (January 2014) - Chapurlat, Roland D
Abstract : Introduction: The market of antiosteoporosis drugs has been declining in recent years, possibly in part due to the publicity around adverse events observed with bisphosphonates. Also, the proportion of patients with clinical fracture who receive adequate treatment remains low. Hence, there are still unmet needs in this field.Odanacatib is a cathepsin K inhibitor currently being developed for the treatment of postmenopausal osteoporosis that could be an advance in this context. Area covered: Odanacatib is a bone resorption inhibitor, but it preserves some degree of bone formation, which differentiates this new family of drugs from existing therapies. Odanacatib increases bone mineral density (BMD) at the spine and hip, improves bone strength estimated using finite element analysis (FEA) at the spine and hip as well as at the distal tibia and radius. The safety profile has been satisfactory so far. A robust antifracture efficacy has been announced when the Phase III pivotal trial had been terminated after interim analysis, but we do not yet have access to the complete results. Expert opinion: Odanacatib may have an important role in future guidelines if it provides a substantial advantage compared to the effective and inexpensive current generic drugs, in terms of antifracture efficacy or safety.